51‐1: Invited Paper: The International Commission on Illumination (CIE) and Aspects of Measurement Uncertainty in Photometry. Issue 1 (28th June 2021) - Blattner, Peter
Abstract : The International Commission on Illumination (CIE) is the umbrella organization of the various national lighting societies. On the one hand it is a standardization authority, on the other hand it is also a scientific organization. This article shows current fields of activity that are relevant for the display industry and provides some information about the concept of measurement uncertainty also applicable to the measurement of displays.